The Fink Active Learning Model For Scouting Concept Acquisition And Retention - Alan Naif Nabi; Rabee Mohammed Salih Suliman; Mohammed Mahdi Mohammed (Jurnal Educative: Journal of Educational Studies, 2026)
Undergraduate scouting education in Iraq continues to rely predominantly on lecture-based instruction, and graduates frequently fail to retain scouting concepts beyond the examination period; moreover, few if any published experimental studies have examined the Fink Active Learning Model within scouting education or any physical education context. This study therefore investigated the effect of the Fink Active Learning Model on the acquisition and retention of scouting concepts among first-year undergraduate students in the Department of Physical Education and Sports Science, University of Zakho, Iraq (academic year 2024–2025). An experimental Equivalent-Groups Post-Test-Only Design with Controlled Observation was adopted. Thirty-six male first-year students were assigned, by lottery of intact class sections, to an experimental group (n = 18), taught through the Fink Active Learning Model, and a control group (n = 18), taught through the conventional method. Over a ten-week intervention comprising 20 teaching units, both groups studied identical scouting content, and learning was measured with a validated 45-item multiple-choice Scouting Concepts Test administered immediately after the intervention (acquisition) and again two weeks later (retention). Mann–Whitney U tests revealed statistically significant differences favouring the experimental group in both concept acquisition (U = 68.5, z = −2.96, p = .003, r = .49, medium effect) and retention (U = 49.0, z = −3.58, p < .001, r = .60, large effect); the experimental group's descriptive retention rate was also higher (93.52% vs. 88.80%). The findings extend the empirical evidence base of the Fink Model into scouting education and physical education, and support the value of structured, experiential, and dialogic active learning designs for promoting durable conceptual learning in these fields.